2022
DOI: 10.1038/s41598-022-18811-7
|View full text |Cite
|
Sign up to set email alerts
|

A shared numerical magnitude representation evidenced by the distance effect in frequency-tagging EEG

Abstract: Humans can effortlessly abstract numerical information from various codes and contexts. However, whether the access to the underlying magnitude information relies on common or distinct brain representations remains highly debated. Here, we recorded electrophysiological responses to periodic variation of numerosity (every five items) occurring in rapid streams of numbers presented at 6 Hz in randomly varying codes—Arabic digits, number words, canonical dot patterns and finger configurations. Results demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous studies have demonstrated the automatic extraction of magnitude information from symbols in adults with frequency-tagging EEG centered around the right posterior sensors 23 33 , while in the present children study, the oddball responses were balanced bilaterally. One previous study found left lateralized SSR by when using number words and a combination of number words and digits in adults 34 .…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have demonstrated the automatic extraction of magnitude information from symbols in adults with frequency-tagging EEG centered around the right posterior sensors 23 33 , while in the present children study, the oddball responses were balanced bilaterally. One previous study found left lateralized SSR by when using number words and a combination of number words and digits in adults 34 .…”
Section: Discussionmentioning
confidence: 56%
“…This stimulus set created the highest amount of diversity within numeral exemplars (20 colored, hand-drawn per numeral), while decreasing the variability across numerals (each schema was applied to all numerals). Increasing variability intra-numerally and decreasing variability inter-numerally might decrease the relative importance of the latter, leading to a smaller impact of visual differences across numeral sets (e.g., Thorpe et al, 1996;Foldiak et al, 2004;Rossion et al, 2015;Georges, Guillaume & Schiltz, 2020;Marlair, Crollen & Lochy, 2022). We propose that increasing variability, such as modeled most strongly by the 20 font stimulus set here, is therefore a promising avenue in future research targeting conceptual processing.…”
Section: Identifying Conceptual Responses To Parity With Variable Sti...mentioning
confidence: 79%
“…In the 10 font set, the variable fonts Agency FB, Segoe Print, Informal Roman, Poor Richard, Gloucester MT Extra Condensed, Forte, Pristina, OCR A Extended, Vladimir Script, and Haettenschweiler were used, so that there were 10 exemplars of each numeral. Note that including variability by changes in font has been applied in previous studies with Arabic numerals (e.g., Cohen, 2009;Vogel, Goffin & Ansari, 2015;with EEG: Lochy & Schiltz, 2019;Finke et al, 2021;Marlair, Crollen & Lochy, 2022). The 10 mixed set was also comprised of 10 exemplars of each numeral, but designed to include even more variability across exemplars that included both fonts and drawings.…”
Section: Stimulus Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…If this is correct, future work should identify how many different items should be used in order to avoid these statistical learning effects. Since there are areas of research in which it is not possible to use many different items (e.g., in numerical cognition, when using Arabic digits as stimuli, there are maximum 10 elements (1 to 9, and 0)), future studies with FPVS-oddball like paradigms should be particularly careful, using changes in surface features of the stimuli to reduce/eliminate mere statistical regularity effects (see e.g., Marlair et al, 2022).…”
Section: Discussionmentioning
confidence: 99%